Q. 5 B5.0( 1 Vote )

# Solve the following equations :tan x + tan 2x = tan 3x

Ideas required to solve the problem:

The general solution of any trigonometric equation is given as –

• sin x = sin y, implies x = nπ + (– 1)ny, where n Z.

• cos x = cos y, implies x = 2nπ ± y, where n Z.

• tan x = tan y, implies x = nπ + y, where n Z.

given,

tan x + tan 2x - tan 3x = 0

In order to solve the equation we need to reduce the equation into factor form so that we can equate the ratios with 0 and can solve the equation easily

As if we expand tan 3x = tan ( x + 2x) we will get tan x + tan 2x common.

tan x + tan 2x - tan 3x = 0

tan x + tan 2x - tan (x + 2x) = 0

As, tan (A + B) =

tan x + tan 2x -

tan x + tan 2x = 0 or – tan x tan 2x = 0

Using, tan 2x = we have,

tan x = tan (-2x) or

tan x = tan(-2x) or tan x = 0 = tan 0

if tan x = tan y, implies x = nπ + y, where n Z

x = nπ + (-2x) or x = mπ + 0

3x = nπ or x = mπ

….ans

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Interactive Quiz on trigonometric identities & equations52 mins
Conditional IdentitiesFREE Class
Trigonometric Functions - 0152 mins
Trigonometric Series45 mins
Trigonometric Functions - 0568 mins
Trigonometric Functions - 0658 mins
Trigonometric Functions - 0366 mins
Interactive Quiz on trigonometric ratios & identities73 mins
Trigonometric Functions - 0268 mins
Trigonometric Functions - 0466 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses